ANALYSIS TECHNOLOGY OF MONITORING COMPUTER NETWORKS. - Гузій, М. М.; Станіславова, О. В.; Кадет, М. В. (Science-based technologies, 2009)
The problem of computer’s monitoring is considered. General system’s requirements are determined. Structure, software requirements and also systems of computer’s network are described in the article.